Development of Digital MSMEs in Facing the Era of Digitalization in the Bengkulu City Area - Hakim, Lukman; Puspa Wulandari, Jenny; Khadafi, M. Prayudha; Yustati, Herlina (Sharia Economic and Management Business Journal (SEMBJ), 2023)
Digital transformation is essential for today's growing business world because it can shorten time, money, and reduce funds. However, it can also be a challenge if businesses do not adapt to change. To overcome this, it is important to take an optimistic and proactive stance. Bengkulu City, one of the major cities in Indonesia, has considerable potential for the development of MSMEs (Municipal Unit). However, there are still many MSMEs that have not utilized digital technology optimally, posing a threat to both the local government and MSME players. Factors that influence digitalization include the ease of conducting business transactions online, the need for business expertise, and profitability. To overcome these problems, the business world needs to adapt to the digital era by utilizing information and telecommunications technology in carrying out its business activities. The transition to rapid digitalization requires businesses to adapt and adjust to change. For MSMEs, the digitalization process requires many steps to encourage digitalization and make it easier for them to adapt. The increasing use of digital and the internet is a big challenge for MSMEs if they want to succeed in the business world. Strategies to overcome this include increasing digital literacy among MSME users, promoting digital literacy among MSME users, and promoting digital literacy among MSME users.